Frozen world : polar meltdown - Callery, Sean. (Mankato, Minn. : Capstone Press, 2008)
Presents the science behind world climate changes, including causes and possible solutions.
Sea change -- Heating up -- Who did it? -- Chop till we drop -- Shrinking ice caps -- A fresh problem -- Can't bear it -- Krill killer -- What a gas -- The Earth's revenge? -- Death rays -- Tube journey -- Action! -- Glossary.
Includes bibliographical references (p. 31), filmography (p. 31), and index.
Horn Book.
Science and Children (N.S.T.A.).
Horn Book, October 2009.
Science and Children (N.S.T.A.), February 2010.
5.4
Keywords: Global warming -- Juvenile literature; Global warming; Global warming